Transformational change to reduce deforestation and climate change impacts – A review of definitions, concepts and drivers in scientific and grey literature - Atmadja, S.; Martius, C.; Leonard, S.; Sanz Sanchez, M.J. (Food and Agriculture Organization of the United Nations, 2021)
Addressing enormous challenges from environmental and climate change requires a transformational change in how we use land and natural resources. This study, jointly undertaken by FAO and CIFOR, investigates how transformational change is understood in the scientific literature. We screened 111 scientific articles, published between 2000 and 2018 on transformational change in health, business and land use, natural resources, and climate change. TC is well articulated in the health, education and business management literature, but less so – only 22 papers – in agriculture, forestry, land use and climate change. Definitions of transformational change converge in that it represents a movement away from the current status; that the transformations should focus on root causes to be sustained; and of a key role of knowledge as driver and indicator of change. Critical elements of TC comprise collective, interdisciplinary and transdisciplinary learning and reflection; managing risks; engaging in on-linear thinking; participation, ownership, and finance. Transformational change is influenced by four groups of drivers: processes; resources; norms; and legitimacy. There are trade-offs between the three dimensions of transformational change: scale, speed (fast) and depth (deep). Indicators of transformational change are complex and difficult to measure. Further reflections and scientific analysis are needed on drivers of transformational change at the intersection between land use and climate change.